Effect of endoscopic treatment in patients with secondary sclerosing cholangitis. Issue 10 (18th August 2022) - Zhang, Chengcheng Christine; Sauer, Peter; Rupp, Christian
Abstract: Background and Aim: Secondary sclerosing cholangitis (SSC) is a progressive disease with high mortality and characterized by chronic inflammation and biliary obstruction. Therapeutic options are limited. The aim of this retrospective study was to evaluate the effects of endoscopic treatment in patients with SSC, the outcome, and association with potential risk factors. Methods: Data from all patients with SSC from 1996 to April 2021 were included. Results: Eighty patients with SSC were included. Seventy‐five patients (93.8%) underwent diagnostic endoscopic retrograde cholangiography; 46 patients (57.5%) could be treated endoscopically. Endoscopic treatment comprised removal of biliary casts ( n = 36/75), dilatation of bile ducts ( n = 17/75), and intermittent stenting ( n = 11/75). Twenty patients underwent orthotopic liver transplantation (25%); 27 patients died (33.8%). Transplantation‐free survival was affected neither by endoscopic treatment nor by presence of biliary strictures, but bacteria positive bile culture was associated with better and increased levels of serum alkaline phosphatase and bilirubin levels with poor outcome. Conclusions: Secondary sclerosing cholangitis is a progressive disease with poor long‐term prognosis. Endoscopic treatment options seem to be limited regarding transplantation‐free survival but might improve quality of life and prevent local complications such as cholangitis. The observed limited effect of endoscopic treatment might be attributed to the rapid progression of this disease.